Rôle de la littérature dans le développement de la compétence communicationnelle en cours d’allemand au Burkina Faso - Jean-Claude Bationo (Multilinguales)
The first function of every language is communication. We can support the thesis that teaching German as a foreign language in Burkina Faso pursues as a fundamental objective the development of the learners’ ability to communicate orally and in writing. More exactly, because each communication is an interactive process between interlocutors, we expect that the assimilation or the use of the German language enables the learners to understand, to exchange ideas, to share their visions of the world. In this way the German language like any language, when it is practised, is an establisher of a community. If on the one hand we define literature as the representation of a created world or an invented existence and on the other hand as imagination, ambiguity and aesthetics or as original creation, constituted by words and ideas, we can then ask the question to know in which measure it could play a role in the process of the learning and the teaching of German as a foreign language. The question is to know if literature facilitates and optimizes the communicative skill. Through the present reflection, we try to answer this question.